The Influence of Recommendations in Social Media on Purchase Intentions of Generations Y and Z - Pauliene, Rasa; Sedneva, Karina (Organizations and Markets in Emerging Economies, 2019)
The aim of this study is to explore how the impact of recommendations in social media on intention to purchase varies between generations Y and Z. The research focuses on two types of online recommendations, namely online reviews and opinion leaders’ recommendations, and e-WOM, which refers to recommendations made by followers. It also aims to examine which of the two types predominates among generations. Based on various studies, a theoretical research model was developed as well as quantitative and qualitative research was employed. The research findings supported the idea that social media recommendations have an influence on purchasing intentions of consumers, however, the main managerial applications of this study are connected with the differences among consumers. Online reviews had been an influential source of information for Generation Y; however, it is losing its influential power towards shaping purchasing intentions. E-WOM is still important, thus brands and retailers are advised to develop and maintain branded communities in social media, encourage their consumers to share feedback not only in social media, but also in rating websites, apps and services. Retailers are advised to segment their target audience very carefully, as differences in generations’ social media habits and information adoption exist.